DEVELOPING ENGLISH READING MATERIALS THROUGH QUANTUM LEARNING MODEL FOR LIGHT MOTOR VEHICLE ENGINEERING STUDENTS IN SMK NEGERI 1 PERBAUNGAN - Muvidah Muvidah; I Wayan Dirgayasa Tangkas; Eddy Setia (LINGUISTIK TERAPAN, 2018)
The purpose of this study are; 1) to examine the existing reading materials used today by the students of light motor vehicle program; 2) to find out the reading materials needed by the students of light motor vehicle program; 3) to develop the reading materials students of light motor vehicle program based on quantum learning model.  This study is descriptive qualitative research. This study inspired by ten stages of Educational Research and Development model by Gall, Gall and Borg, 2003, but in implementing the model is simplified and adapted to Dirgayasa (2011) become four steps: 1) Evaluation and need analysis, 2) designing new material, 3) validating material, 4) revision and final production. The Instrument of collecting the data was collected by questionnaire, documentation and interview. The result of this study showed that the students agree that they really need the relevant material which proper to their program and the analysis of the existing reading material and the existing syllabus showed that the both are less relevant for English reading skill for light motor vehicle students. From evaluation research of documentation and interview agreed that the developing of reading material for light motor vehicle is needed combined with the quantum learning model. the final result of this developing material through quantum learning become some activities; enrolling, experience, labeling, demonstration, review and celebrate and with new title which has correlation with light motor vehicle program they are: 1) Introduction world of automotive;, 2) Introduction to tools used by mechanics; 3) Safety rules automotive maintenance safety; 4) How cars work; 5) Light vehicle clutch system; 6) General maintenance. Keywords: reading materials, light motor vehicle program, quantum learning model.